An Approach to Identify Nerve Injury-Evoked Changes that Contribute to the Development or Protect Against the Development of Sustained Neuropathic Pain - Recio-Pinto, Esperanza; Norcini, Monica; Blanck, Thomas J.J. (IntechOpen, 2012)
None